A COMPARATIVE ANALYSIS OF CAMBRA AND MINDTAIN MOBILE APPLICATIONS IN ASSESSING RISK OF PERMANENT DENTAL CARIES IN CHILDREN AGED 6-12 YEARS: A CROSS-SECTIONAL STUDY AT MADRASAH IBTIDAIYAH MA’ARIF 1 AND 2 SUKUN, MALANG CITY - Balbeid, Merlya; Sabrina, Qonithah Nur; Hartami, Edina; Priyanto, Rahmavidyanti (Universitas Brawijaya, 2026)
Caries risk assessment in permanent teeth is an important preventive strategy for controlling and managing dental cases in children. CAMBRA is an individual-based method for assessing caries risk, while the MinDTain Mobile App is a digital tool that applies a multilevel approach by considering individual, family, and school environmental factors. This study aims to determine the differences between CAMBRA and the MinDTain Mobile Application in assessing the risk of permanent dental caries in children aged 6–12 years at Madrasah Ibtidaiyah Ma’arif 1 and 2 Sukun, Malang City. This study used a quantitative analytical observational design with a cross-sectional approach. Subjects were selected using the total sampling technique. Data were collected through structured interviews and intraoral clinical examinations using the CAMBRA form and the MinDTain Mobile App. Data were analyzed using the Chi-square test. The results showed a p-value <0.05 in both age groups [6–9 years and 10–12 years], indicating a statistically significant difference in caries risk assessment between the two methods. In conclusion, there is a significant difference in the caries risk assessment results between CAMBRA and the MinDTain Mobile App in children aged 6–12 years.